Pengaruh Promosi, Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Menggunakan Jasa Fotography (Studi Kasus Kevan Photography) - Mukhammad Nurul Huda; N. Rachma; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThe purpose of this study was to determine and analyze the effect of promotion, price, service quality on purchasing decisions. Primary data collection using questionnaires and secondary data collection using a survey of consumers who visited Kevan Photography, Pasuruan. there were 72 consumers as a population. using purposive sampling technique with criteria.The results in this study indicate that there is a simultaneous effect of promotion on purchasing decisions, price affects purchasing decisions, service quality affects purchasing decisions Keywords: Promotion, Price, Service Quality and Purchase Decision